A Generalizable Telerobotic Solution for Undisrupted Man-Robot Workflow Coupling via Shape-Variable Virtual Fixture - Shi, Yunze; Wang, Tengyue; Lei, Chen; Yang, Liangjing (IEEE access, 2025)
This paper introduces a generalizable telerobotic solution for the coupling between manual and machine workflow tracks to facilitate the incorporation of personnel-required procedures in lab automation processes. The proposed shape-variable virtual fixture can be generalized for providing synchronized dexterous guidance during human interaction with a robotized automation process without disrupting the automated workflow. Accuracy performance evaluation showed that the use of our proposed shape-variable virtual fixture reduced positioning and orientation errors by 50%. Stability and transparency are validated by evaluation of the force profiles during the teleoperation process while interacting with the environment. User experience test based on the NASA-TLX evaluation also indicates reduced workload and task complexity experienced by the subjects of informed consent, suggesting better usability with our proposed method. This study demonstrates the feasibility and usability of the proposed telerobotic approach using shape-variable virtual fixtures for generalized man-robot collaborated workflows. It is envisioned that the work would pave a path for the realization of safer and more intuitive human-robot collaboration while maintaining the efficiency of the ever-increasing task complexity in modern smart laboratories.